1989
DOI: 10.1002/ajmg.1320320319
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 10qter deletion syndrome: A review and report of three new cases

Abstract: We report on three patients with terminal deletions of chromosome 10q and compare them to 15 previously reported patients. A similar facial appearance with a prominent beaked nose, large and/or malformed ears, and a pattern of major abnormalities including severe mental retardation, cardiac anomalies, and anogenital anomalies are reviewed. We feel the manifestations of del 10qter are sufficiently distinct to suggest this diagnosis on clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 10 publications
(9 reference statements)
3
87
2
1
Order By: Relevance
“…Seven cases have break points in 10q25 [Lewandowski et al, 1978;Mulcahy et al, 1982;Curtis et al, 1986;Vanlieferinghen et al, 1987;Wulfsberg et al, 1989;Schrander-Stumpel et al, 1991;Chung et al, 1998]. Interstitial deletions involving distal chromosome 10q have been reported in 4 cases [Ray et al, 1980;van de Vooren et al, 1984;Shapiro et al, 1985;Rooney et al, 1989], but only the case reported by Rooney et al [1988] has break points in 10q25 and q26.…”
Section: Introductionmentioning
confidence: 92%
“…Seven cases have break points in 10q25 [Lewandowski et al, 1978;Mulcahy et al, 1982;Curtis et al, 1986;Vanlieferinghen et al, 1987;Wulfsberg et al, 1989;Schrander-Stumpel et al, 1991;Chung et al, 1998]. Interstitial deletions involving distal chromosome 10q have been reported in 4 cases [Ray et al, 1980;van de Vooren et al, 1984;Shapiro et al, 1985;Rooney et al, 1989], but only the case reported by Rooney et al [1988] has break points in 10q25 and q26.…”
Section: Introductionmentioning
confidence: 92%
“…The main clinical features of pure 10p duplication, which were described by Granata et al [2000], are intellectual disability, growth retardation, skull abnormalities (dolichocephaly, microcephaly, wide sutures, high and prominent forehead, microretrognathia, cleft palate), facial dysmorphism (upswept frontal hair pattern, palpebral fissure abnormalities, hypertelorism, nose/lip/ear abnormalities), and finger abnormalities. The clinical features of distal 10q deletion consist of prenatal and postnatal growth retardation, varying degrees of intellectual disability, behavioral disorders, microcephaly, characteristic facial appearance (broad nasal bridge with a beaked or prominent nose, strabismus, hypertelorism, low-set malformed ears), and genital and digital anomalies [Wulfsberg et al, 1989;Chang et al, 2013;Plaisancie et al, 2014]. The breakpoints and the resulting chromosomal alterations in our patient 1 are very close to those detected in 2 patients described by Roberts et al [1989].…”
Section: Discussionmentioning
confidence: 51%
“…The breakpoints for the terminal deletion of chromosome 10 have ranged from 10 q23Նq26.2, and the affected patients have a strikingly similar phenotype with a positive correlation between the increasing severity of their major malformations and the increasing size of their chromosome deletion. 1 Findings from the routine chromosome study of this patient were initially interpreted as normal. However, there was a strong index of suspicion on the basis of the patient's facial features, malformed ears (overfolding of the superior helix, underfolding of the posterior helix, and a prominent tragus), and hands.…”
Section: Diagnosis and Discussionmentioning
confidence: 99%
“…1 This child had a normal renal ultrasonographic scan on her third day of life, but presented with high fever secondary to Escherichia coli bacteremia and urosepsis at 2 months of age. The ultrasonogram of her kidneys at this time revealed a dilated collecting system of the left kidney; a contrastenhanced cystogram showed bilateral reflux and hydronephrosis to the level of the kidneys.…”
Section: Differential Diagnosismentioning
confidence: 99%